The Effect Of Profitability, Liquidity, And Activities On The Financial Performance Of Health Sector Companies At The Idx In 2018-2021 - Rahmawati, Sri; Wuryani, Eni; Isahak, Mohamad Shahril (International Economic Conference of Business and Accounting, 2024)
Company performance can be described by looking at the conditions of financial performance in each company. The purpose of conducting this research is to determine the effect of profitability, liquidity and activity on financial performance in the health sector in 2018-2021. The data used in this research is secondary data. The population in this study are health companies listed on the Indonesia Stock Exchange in 2018-2021. The data is taken from the company's annual report. The sample in this study amounted to 15 companies after being selected using a purposive sampling method. This study uses the analysis technique of classical assumption test, T test, and F test. The analysis is used to prove the hypothesis assisted by SPSS 25 software. The results of this study simultaneously show (Test F) the five independent variables namely Return on Equity (ROE), Net Profit Margin (NPM), Current Ratio (CR), Quick Ratio (QR), Total Asset Turn Over (TATO) have a significant effect on financial performance. Partially (T test), the variables Return on Equity (ROE) and Net Profit Margin (NPM) affect financial performance, while 3 other variables, namely Current Ratio (CR), Quick Ratio (QR) and Total Asset Turn Over (TATO) no effect on financial performance.